Lumpy labor adjustment as a propagation mechanism of business cycles - Fang Yao (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
I explore the aggregate effects of micro lumpy labor adjustment in a prototypical RBC model, which embeds a stochastic labor duration mechanism in the spirit of Calvo(1983), and it extends this approach by introducing a Weibull-distributed labor adjustment process to capture the increasing hazard function corroborated by the micro data. My principal findings are: The aggregate labor demand equation derived from the baseline Calvostyle model corresponds to the same reduced form as the quadratic-adjustment-cost model and deep parameters have a one-to-one mapping. However, this result does not hold in general. When introducing the Weibull labor adjustment, the aggregate dynamics vary with the extent of increasing hazard function, e.g., the volatility of aggregate labor is increasing, but the persistence is decreasing in degree of the increasing hazard of the labor adjustment.
Keywords: E32; E24; C68; 330; Business cycles; heterogeneous labor rigidity; increasing hazard function; Weibull distribution; Konjunkturtheorie; Dynamisches Gleichgewicht; Arbeitsmobilität; Anpassung; Theorie